Florida's Property Tax Reform: Statutory Changes - Rodney L. Clouser; W. David Mulkey (EDIS)
FE704, a 9-page fact sheet by Rodney L. Clouser and W. David Mulkey, is part of the Florida’s Property Tax Reform series. It provides a brief summary of statutory changes made during the June 2007 special legislative session, how they vary in different fiscal years, other statutory changes, and impacts statewide and for individual property owners. Includes references and tables showing reduction levels for fiscal years 2008 and 2009, and county government rollback calculations. Published by the UF Department of Food and Resource Economics, December 2007.